2006
DOI: 10.1002/erv.736
|View full text |Cite
|
Sign up to set email alerts
|

How important are motivation and initial Body Mass Index for outcome in day therapy services for eating disorders?

Abstract: This study was designed to investigate the impact of initial Body Mass Index (BMI) and motivation for recovery on a 12-week day therapy programme for Eating Disorders. Outcome was assessed by changes in eating disorder symptomology, mood and self-esteem. A battery of assessment questionnaires was given to 34 eating disorder clients on admission to and completion of the programme. This study found that BMI at admission did not affect treatment outcome directly. Only patient self-rated motivation directly affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 29 publications
3
41
1
Order By: Relevance
“…Past research has found that a low BMI predicts greater bulimic pathology in patients with anorexia nervosa (AN) at the end of treatment (9) and greater drop out from treatment amongst a sample with either AN or BN (10). The combination of past and current findings on low BMI and on weight suppression suggests that both influences could exacerbate symptoms and undermine treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Past research has found that a low BMI predicts greater bulimic pathology in patients with anorexia nervosa (AN) at the end of treatment (9) and greater drop out from treatment amongst a sample with either AN or BN (10). The combination of past and current findings on low BMI and on weight suppression suggests that both influences could exacerbate symptoms and undermine treatment.…”
Section: Discussionmentioning
confidence: 99%
“…To date, highest weight has not been predictive of BN symptoms or treatment outcome (2, 8). However, current weight is independently predictive of BN symptoms and outcome, with those who have lower weights demonstrating higher rates of BN pathology (9) and higher risk of treatment dropout (10). …”
mentioning
confidence: 99%
“…Hence, although in the current study eating psychopathology was high, participant's 'preparation stage' readiness to change at admission to treatment may have played a role in precipitating improvement in eating disorder symptomatology. Jones, Bamford, Ford, and Schreiber-Kounine (2007) noted that admission motivation indirectly effected DP treatment outcome via influencing how likely a patient was to complete treatment.…”
Section: Discussion Of Readiness To Change Outcomesmentioning
confidence: 99%
“…12,13 In contrast, a key advantage of the decision making model of change is its conceptualization of motivation as multidimensional instead. This multidimensional model is well-suited to assessment of the ambivalence (i.e., simultaneous internalization of both pros and cons of illness) that is common among patients with eating disorders.…”
Section: Introductionmentioning
confidence: 94%